A more scientific blood lead reference value urgently needs to be updated in China: From a national and international insight - Xiaoli Duan; Suzhen Cao; Jiacheng Guan; Ligang Hu; Chengye Sun; Chonghuai Yan; Xiaoli Zhao; Fengchang Wu (Eco-Environment & Health, 2025)
Although blood lead levels (BLLs) in children have significantly decreased compared to two decades ago, incidents of lead poisoning and elevated BLLs among children continue to occur frequently. This trend suggests that China's current hygienic regulations are not sufficiently effective in managing children's lead exposure. This study analyzed the revision processes of blood lead reference values (BLRVs) in children from various countries, the current BLLs and their changing trends in China, potential sources of lead pollution and exposure, the requirements for managing and protecting children's health, as well as the national measures and strategies for lead emission management and control. The study also explored the necessity and urgency of updating China's BLRVs in children. Based on the specific conditions in China, a proposed BLRV of 50 μg/L was deemed more reasonable and was suggested for implementation, with the potential to yield substantial economic benefits through improved IQ outcomes should the updated BLRV be adopted.